Preconception Care and Genetic Counseling: Implications for the Midwife (A Review) (2021)
Many women give birth to babies with various genetic or congenital abnormalities and other complications but are totally unprepared for the experience. These among several others are the negative consequences that could result from poor preconception health which could cause perpetual sorrow in the future. Preconception care and genetic counselling can increase the health and well-being of women and couples and improve subsequent pregnancy and child health outcomes. This paper discusses the issues in relation to preconception care and genetic screening and counselling. Preconception care is beneficial to both low risk and high-risk women in preventing foetal abnormalities and helps to reduce the incidence of foetal anomalies, poor pregnancy outcomes and genetic abnormalities as risk factors would have been noticed and proper counsel given to prevent the occurrence of abnormality. Its long-term outcome also results in healthy women, healthy men, healthy babies, healthy families and healthy societies. Preconception care is a need that should be incorporated into every country's health care system. There should be increased public awareness of the importance of preconception healthcare services by using information and tools appropriate across various ages, literacy, including health literacy; and cultural/linguistic contexts. The midwife has significant roles to play and must have up to date information about preconception care and genetic counselling and screening.